'Border Control and Monitoring "Undesirable" Cypriots in the UK and Australia, 1945–1959'. Issue 1 (4th May 2022) - Varnava, Andrekos
ABSTRACT: This article explores why and how the British and Australian authorities monitored their British Cypriot communities and how this impacted upon their respective immigration policies in connection with British Cypriots. Both the British and Australian authorities monitored sections of the British Cypriot community for similar reasons, especially political, using similar techniques, yet adopted different immigration policies on more Cypriots arriving. While the historiography for this period claims that the British were moving towards restricting immigration from their Empire and Australia was opening its borders, the opposite is in fact the case for the British Cypriots. The British did not alter their policies or procedures very much on the immigration of Cypriots from the 1930s, and even opened their border to Cypriot informers during the EOKA period. On the other hand, the Australian authorities progressively placed restrictions on Cypriots until they suspended immigration in 1956.